Politeness across cultures - Таnasova, N. (My University, 2019)
Politeness as a social phenomenon is a significant aspect of communication. It is observed in “the very heart of social life and interaction” and considered to be “a precondition for human cooperation in general” [1, p. 326]. A Dictionary of Linguistics and Phonetics defines politeness as “norms of social behaviour, in relation to such notions as courtesy, rapport, deference and distance” [2, p. 373]. According to P. Brown, politeness is “a concept designating ‘proper’ social conduct, rules for speech and behaviour” [1, p. 326]. This notion is also described as a means “to maintain the kind of smooth, harmonious interpersonal relationships called for by any human community” [4, p. 97].
Keywords: politeness; intercultural interaction